Contributions to national-level policy discourse on response to economic impacts of COVID-19 in Ghana, Malawi, Tunisia and Indonesia - CGIAR Research Program on Policies, Institutions, and Markets (2020)
In Ghana, Indonesia, Malawi and Tunisia, IFPRI researchers’ work on the economic impacts of COVID-19 based on PIM modeling tools was presented to high-level policy makers and significantly helped shape national-level policy discourse.